New limits on anomalous contributions to the Wtb vertex - Birman, J. L. (2016)
The latest and most precise top quark measurements at the LHC and Tevatron are used to establish new limits on the Wtb vertex. Recent results on the measurements of the W-boson helicity fractions and single top quark production cross section are combined in order to establish new limits at 95% CL (confidence level). The allowed regions for these limits are presented, for the first time, in three-dimensional graphics, for both real and imaginary components of the different anomalous couplings, providing a new perspective on the impact of the combination of different physics observables. These results are also combined with the prospected future measurement of the single top quark production cross section and W-boson helicity fractions at the LHC.